(untitled) (Revista de Artes Marciales Asiáticas, 2022)
The aim of this study was to investigate the teaching path and identify the construction of knowledge by university teachers for teaching martial arts and combat sports. This is a descriptive study with a qualitative approach, in which participated seven higher education teachers who taught martial arts and combat sports in undergraduate courses in Physical Education. Narrative interview was used as data collection technique. Data analysis was carried out using content analysis technique, with categories organized both a priori (training and professional path) and posteriori (involvement with martial arts and combat sports and knowledge about the content of martial arts and sports combat). Results showed the participants’ involvement with martial arts and combat sports along their trajectories, and some participants considered the experience of practicing martial arts and combat sports as an important knowledge for teaching. The teachers considered as limitations for teaching not having expertise in martial arts and combat sports, the lack of bibliography on martial arts and combat sports teaching, and not being full professor of the subjects that they were teaching. On the other hand, the results looked beyond the teaching of martial arts and combat sports techniques, embracing historical, social and game-oriented aspects. Based on the theory of the “knowledge base for teaching”, this study points outs that teachers tend to consider the different types of knowledge to support teaching, however, they still need to reflect on their trajectory and improve and transform their knowledge bases, aiming to a teaching that breaks with the problems pointed out by the literature and by the participants.